False aneurysms of the thoracic aorta: anastomosis investigation using the inflation-extension test - Rečičárová, Sandra; Chlup, Hynek; Jonák, Michael; Netuka, Ivan (Journal of applied biomedicine, 2023)
INTRODUCTION: False aneurysms in the thoracic aorta are dangerous complications that can occur after cardiac surgery. They often result in high mortality rates. These aneurysms are caused by damage to all layers of the aortic wall. This study aimed to pinpoint the area of the experimental specimen (native vessel, anastomosis, or prosthetic graft) with the greatest deformation, to determine whether a false aneurysm is likely to develop in the anastomotic portion. METHODS: We conducted the inflation-extension test by performing eight cycles ranging from 0 to 20. The pressure sampling frequency was 100 Hz, and each cycle lasted approximately 34 seconds, resulting in a loading frequency of 0.03 Hz. During the experiment, each camera captured 3,000 frames. Based on the data collected, we evaluated and compared the loading stages of cycle 1 and cycle 8. RESULTS AND DISCUSSION: During loading, the native vessel experienced a dominant deformation of approximately 7% in the circumferential direction. The prosthetic graft, which had a longitudinal construction, deformed by approximately 8% in the axial direction. The prosthetic graft, on the other hand, only experienced a deformation of up to 1.5% in the circumferential direction, which was about 5 times smaller than the deformation of the native vessel. The anastomosis area was very stiff and showed minimal deformation. Additionally, there was little difference in the mechanical response between the first C1 and the eighth C8 cycle. CONCLUSION: Based on the available evidence, it can be inferred that aortic false aneurysms are more likely to form just behind the suture lines in the native aorta, which is more elastic compared to stiff sections of anastomosis and prosthetic graft. Numerous pulsations of the native vessel will likely cause the impairment of the aorta at the margin of the anastomosis. This will lead to disruption of the aortic wall and false aneurysm formation in the native vessel near the area of anastomosis.
Keywords: aortální aneurysma; lidé; nepravé aneurysma; anastomóza chirurgická; Aneurysm, False; Aorta, Thoracic; Anastomosis, Surgical; Aortic Aneurysm; aorta thoracica; Humans